2014
DOI: 10.1099/mic.0.077586-0
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for specificity annotation shows a distinct evolutionary divergence among the microbial enzymes of the cholylglycine hydrolase family

Abstract: Bile salt hydrolases (BSHs) are gut microbial enzymes that play a significant role in the bile acid modification pathway. Penicillin V acylases (PVAs) are enzymes produced by environmental microbes, having a possible role in pathogenesis or scavenging of phenolic compounds in their microbial habitats. The correct annotation of such physiologically and industrially important enzymes is thus vital. The current methods relying solely on sequence homology do not always provide accurate annotations for these two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In contrast, Panigrahi et al (2014) have observed the presence of an indel mutation in the loop region of CGH from Gram-negative bacteria shortening the loop.…”
Section: Quaternary Structure and Inter-subunit Interactionsmentioning
confidence: 81%
See 2 more Smart Citations
“…In contrast, Panigrahi et al (2014) have observed the presence of an indel mutation in the loop region of CGH from Gram-negative bacteria shortening the loop.…”
Section: Quaternary Structure and Inter-subunit Interactionsmentioning
confidence: 81%
“…In conclusion, we have resolved the structure of a functional penicillin V acylase from the Gram-negative plant pathogen P. atrosepticum, which shows high specific activity for Pen V. Panigrahi et al (2014) have reported the classification of choloylglycine hydrolases from Gram-positive and Gram-negative bacteria into different clusters, based on a new binding site profile-based scoring system. The two groups show low sequence homology (<30%) and significant structural differences, including the loss of the tetramer assembly motif and inclusion of a periplasmic signal pre-peptide in Gram-negative CGHs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Loop1, loop2 and loop3 allowed the entry of substrates into the active site of the enzyme and referred as 'Site A', whereas the site of glycine release is referred to as Site L as shown below ( Fig. 1b) (Panigrahi, Sule, Sharma, Ramasamy, & Suresh, 2014;Rossocha et al, 2005). With few exceptions, most of the gram positive and gram negative organisms possess the tetrameric form of BSH.…”
Section: Introductionmentioning
confidence: 99%
“…With few exceptions, most of the gram positive and gram negative organisms possess the tetrameric form of BSH. Distinct clustering of gram positive and gram negative bacterial BSH were observed owing to indel mutation (20)(21)(22) amino acids) in the tetramer loop region (Panigrahi et al, 2014). Theoretical prediction states that the presence of tetramer loop provides thermostability to gram positive BSHs as compared to gram-negative BSHs (Panigrahi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%